2017
DOI: 10.1002/ecs2.2009
|View full text |Cite
|
Sign up to set email alerts
|

Short‐ and long‐term effects of a single application of two organic amendments

Abstract: A frequent side-effect of soil treatment with organic amendments is the slow release of harmful metals deriving from the initial matrices, mainly municipal waste and manure from intensive farming. Contamination is amplified by repeated treatments, which is a common practice to maintain soil fertility. The aim of the present research was to compare, in a mesocosm trial, short (one year)- and long-term (ten years) effects of a single application of compost or a mixture of compost and poultry manure to limestone … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 47 publications
0
11
0
Order By: Relevance
“…The use of soil organic amendments, such as biowaste compost (BC) or sewage sludge (SS), is a sustainable agricultural practice presenting two advantages: on the one hand, it supplies valuable nutrients (e.g., nitrogen and phosphorus) and organic matter to agricultural soil, and on the other hand, it allows the reutilization of by-products of waste treatment plants. Compost addition is the most employed land management practice for the accumulation of organic carbon in soils [7,8], while providing plants with essential nutrients [9][10][11]. Long-term soil amendments with biowaste compost, alone or in combination with mineral fertilizers (MFs), may represent a cost-effective, eco-friendly, and safe strategy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…The use of soil organic amendments, such as biowaste compost (BC) or sewage sludge (SS), is a sustainable agricultural practice presenting two advantages: on the one hand, it supplies valuable nutrients (e.g., nitrogen and phosphorus) and organic matter to agricultural soil, and on the other hand, it allows the reutilization of by-products of waste treatment plants. Compost addition is the most employed land management practice for the accumulation of organic carbon in soils [7,8], while providing plants with essential nutrients [9][10][11]. Long-term soil amendments with biowaste compost, alone or in combination with mineral fertilizers (MFs), may represent a cost-effective, eco-friendly, and safe strategy [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that shorter periods of cultivation do not have significant effect on soil quality as reported in the literature (Lazcano et al, 2013). However, over long periods the continuous uses of manures have had a significant effect on soil quality (Memoli et al, 2017). Van-Camp et al, (2004) found that organic amendments influence soil characteristics by the interdependent modification of biological, chemical and physical properties.…”
Section: Soil Qualitymentioning
confidence: 94%
“…Organic amendments also influence soil chemical properties in a positive way. Indeed, their favorable effects on soil microbial communities are often linked to changes in soil chemical characteristics [50,51]. Several organic amendments may have a direct effect on soil fertility by providing a wide variety of macro-and micro-nutrients, which support plant and microbial growth [52].…”
Section: Organic Residues As Soil Amendments 21 Origin Characteristics and Impact On Soil Propertiesmentioning
confidence: 99%
“…Some of the potential negative effects analyzed and determined in the literature are the increase in soil electrical conductivity and its salinization, negative impacts on the sensitivity and resilience of soil bacteria communities, and the release of pollutants into the soil and/or waters (nitrate, heavy metals, antibiotics, polycyclic aromatic hydrocarbons, dioxins, PCBs, etc.) [51,[59][60][61][62][63].…”
Section: Organic Residues As Soil Amendments 21 Origin Characteristics and Impact On Soil Propertiesmentioning
confidence: 99%